2020
DOI: 10.5377/innovare.v9i2.10207
|View full text |Cite
|
Sign up to set email alerts
|

Efectos de módulos fotovoltaicos en la carga térmica de un edificio industrial

Abstract: Introducción: Hay pocas consideraciones en los beneficios indirectos que proporciona la instalación de sistemas fotovoltaicos. El objetivo del estudio fue analizar la influencia de módulos solares fotovoltaicos (FV) instalados sobre techo en la carga térmica de un edificio industrial en Choloma, Honduras. Métodos: El estudio se realizó mediante la instalación y verificación de sensores de temperatura en las caras exterior e interior del techo de área de descarga del edificio antes y después de la instalación d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Recently, Ochoa [7] identified that using photovoltaic panels in an industrial Choloma building in Honduras reduced the building's exterior roof temperature by up to 24.3%. The resulting thermodynamic analysis showed an 83.8% reduction in total roof heat gain and a 28.1% reduction in overall building heat gain.…”
Section: Strategy 2: Hvac System Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Ochoa [7] identified that using photovoltaic panels in an industrial Choloma building in Honduras reduced the building's exterior roof temperature by up to 24.3%. The resulting thermodynamic analysis showed an 83.8% reduction in total roof heat gain and a 28.1% reduction in overall building heat gain.…”
Section: Strategy 2: Hvac System Efficiencymentioning
confidence: 99%
“…However, this work does not consider PV system placement an efficiency strategy. According to [7], rooftop solar systems are more profitable when there is a separation between the roof and the solar panels to avoid overheating due to ventilation. Similarly, the slope and distance between the modules are important factors affecting the thermal performance of the building.…”
Section: Introductionmentioning
confidence: 99%